The one to one future : - Peppers, Don
Today, technology allows us to sell more goods to fewer people, which is far more efficient than selling fewer goods to more people. Peppers, an advertising executive, and Rogers, a marketing scholar, set out their new marketing paradigm in detail. A one-to-one competitor focuses on "share of customer" rather than the mass-marketer's "share of market." Learn to collaborate with the customer to build loyalty and build your opportunities for future profit